2018
DOI: 10.3390/ijms19071957
|View full text |Cite
|
Sign up to set email alerts
|

Hamster Melatonin Receptors: Cloning and Binding Characterization of MT1 and Attempt to Clone MT2

Abstract: For many years, it was of interest to identify the sequences encoding the two melatonin receptors (MT1 and MT2) from various species. After publishing the basic molecular characterization of the human, rat, mouse, sheep, and platypus MT1, MT2, or Mel1c receptors, we began cloning the genes from other animals, such as birds, bats, and vipers. The goal was to advance the receptor crystallization, which could greatly contribute the understanding of the sequence/stability relationship. European hamster MT1 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This group further showed that Syrian hamsters were a natural knockout organism for this MT 2 receptor subtype (Weaver et al, 1996). Our group recently confirmed the pharmacologic characteristics of the hamster MT 1 receptor, as well as the difficulty of obtaining the MT 2 receptor from European hamsters (Gautier et al, 2018a), although it is probably not knocked out in this subspecies of hamster.…”
Section: Introductionsupporting
confidence: 57%
“…This group further showed that Syrian hamsters were a natural knockout organism for this MT 2 receptor subtype (Weaver et al, 1996). Our group recently confirmed the pharmacologic characteristics of the hamster MT 1 receptor, as well as the difficulty of obtaining the MT 2 receptor from European hamsters (Gautier et al, 2018a), although it is probably not knocked out in this subspecies of hamster.…”
Section: Introductionsupporting
confidence: 57%
“…To compare these data with those from oMT 1 and oMT 2 , we investigated the behavior of 16 other compounds (Fig. 1) coming from the standard characterization of our cloned MLT receptors as reported in recent years for human (Audinot et al, 2003), rat (Audinot et al, 2008), mouse (Devavry et al, 2012), sheep (Cog e et al, 2009 and hamster MLT receptors (Gautier et al, 2018) as well as some compounds from the general safety pharmacology profile. Under our experimental protocol, only MCA-NAT, 5-HT, Ket, DOI, DA, and NA did not compete with the tracer (n = 2 for pars tuberalis membranes and n = 4 for hypothalamus membranes).…”
Section: Resultsmentioning
confidence: 99%
“…In these circumstances, it was obviously the human genes. But the foreseen use of various animal models such as rat, 39 hamster 40 and mice, 41 as well as sheep, 42,43 as a diurnal animal model, was necessary to assess the effect of new ligands on stress and depression. 44 If in some cases, the cloning of those genes was already reported, their pharmacological profiles were poorly described using a large panel of molecules.…”
Section: Tools: the Gene And The Proteinmentioning
confidence: 99%